USIM’s Smart University Blueprint: Advances and Challenges - Saudi, Madihah Mohd; Talib, Ramlah (Journal of Sustainability Perspectives, 2023)
COVID-19 and the movement control order (MCO) implemented in 2020 and 2021, have had a major impact on Universiti Sains Islam Malaysia (USIM) in all directions. To mitigate these problems, USIM’s top management has taken several initiatives to ensure the operation of the University is upheld to its most so that the student continue their study without any delay or obstruction. By incorporating the United Nations’ Sustainable Development Goals (SDGs) on Goal 4 (focused on inclusive and equitable quality education) and with the underlying concept of data-driven and student-centric, this paper presents Smart University Blueprint (Al-Jamiah Al-Mubarakah). It has 5 clusters and 13 initiatives for digital transformation to support inclusive and equitable quality education. The 5 clusters consist of smart governance, smart lifestyle, smart infrastructure, smart learning, and smart services. This smart blueprint is based on 7 principles from USIM’s ICT Strategic Plan (ISP) 2021-2025, which emphasized and are based on the Islamic Laws concept (Maqasid Syariah), Industrial Revolution, Student-Centric, Data-Driven, Open Source, Agile and Mobility, and Prosumers. This paper presents how the blueprint has helped to accelerate stakeholders’ understanding and cooperation in achieving SDGs in higher education during and beyond the pandemic.